(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Laparoscopic cholecystectomy (LC) is the gold standard for treating symptomatic gallstone disease, offering reduced pain, shorter hospital stays, and better cosmesis than open surgery. However, port site infections (PSIs), superficial surgical site infections at trocar insertion sites, remain a common complication, affecting 1-10% of cases globally and 5-8% in India. Risk factors include obesity, diabetes, bile spillage, and emergency procedures. This thesis investigates PSI incidence, predictors, and outcomes in a tertiary center. Aims and Objectives: Evaluate PSI incidence, risk factors, and outcomes post-LC. Objectives: Determine PSI rates in elective/emergency cases; identify patient (age, BMI, comorbidities) and procedural (operative time, spillage) factors; assess microbiological profiles; analyze impacts on recovery; recommend prevention strategies. Materials and Methods: Prospective observational study at Medical College and Hospital, Kolkata (Feb 2021–Jan 2023) involving 200 LC patients (18-70 years). Inclusion: Benign gallbladder disease. Exclusion: Malignancy, prior surgery. Data: Preoperative assessments, perioperative details, postoperative monitoring using CDC criteria. Swabs cultured for pathogens. Statistics: SPSS; chi-square, t-test, logistic regression (p<0.05). Result and Analysis: PSI incidence: 6% (12/200), mostly epigastric port (58.3%). Significant risks: Obesity (OR 4.2, p<0.001), diabetes (OR 3.1, p=0.02), bile spillage (OR 5.6, p<0.001), prolonged surgery (p=0.002). Pathogens: E. coli (40%), S. aureus (30%). Hospital stay prolonged (8.5 vs. 2.3 days, p<0.001). Discussion: PSI rate aligns with literature; epigastric predominance due to extraction trauma. Obesity/diabetes impair healing; spillage introduces biliary bacteria. Empirical antibiotics effective, but resistance rising. Limitations: Single-center; suggests retrieval bags and optimization. Conclusion: PSIs affect 6% of LCs, prolonging recovery. Key predictors: Obesity, diabetes, spillage. Preoperative control and procedural refinements reduce risks, improving outcomes.